2010
DOI: 10.1016/j.drugalcdep.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Psychopharmacological effects of oxycodone in healthy volunteers: Roles of alcohol-drinking status and sex

Abstract: Background-Studies have shown that alcohol-drinking status modulates psychopharmacological effects of several drugs. We sought to determine if drinking status modulates the effects of a prescription opioid, oxycodone, in healthy volunteers. We included sex of the volunteer in the statistical analyses since this is a factor that is known to alter several pharmacodynamic effects of opioids in nonhumans and humans.Methods-Fifteen light drinkers (eight males) and 14 moderate drinkers (eight males) participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 49 publications
1
25
1
Order By: Relevance
“…This finding is in agreement with the results of other studies. [10][11][12] Clinicians need to be alert to the greater risk of opioid-induced nausea or vomiting among women.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with the results of other studies. [10][11][12] Clinicians need to be alert to the greater risk of opioid-induced nausea or vomiting among women.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mean bioavailability for the 15 mg/70 kg dose was 79.5% for females and was 76.5% for males (Lofwall et al, 2011). Several studies have reported that women have more nausea and episodes of vomiting than males after opioid administration, in particular with morphine (Fillingim et al, 2005; Sinclair et al, 1999; Zacny, 2002), but this gender difference is less consistent after oxycodone administration (Zacny and Drum, 2010; Zacny and Gutierrez, 2003, 2009) among non-drug abusing volunteers. Notably, in the current study, despite more vomiting among females, there were no gender differences in ratings of bad effects.…”
Section: Discussionmentioning
confidence: 99%
“…In non-drug-abusing healthy volunteers, a number of studies have shown that prescription opioids at supratherapeutic doses impair performance on various cognitive and psychomotor tests, including the Digit Symbol Substitution Test (DSST) ([68]), the Baddeley Logical Reasoning Test ([2]), and the Maddox Wing Test ([26]) (e.g., [11]; [48]; [69]; [70]; [71]). In contrast, a number of studies primarily using a computerized version of the DSST ([47]) showed that performance was not impaired after parenteral administration of various full mu agonists, partial mu agonists, and mixed action agonists in non-dependent heroin users (e.g., [27]; [49]; [50]; [51]).…”
Section: Cognitive and Psychomotor Performancementioning
confidence: 99%